Attitudes in Russia to social and political aspects of human trafficking, 2007 - Buckley, Mary (UK Data Service, 2010)
The project collected representative data across Russian regions on attitudes to human trafficking. Since the collapse of the Soviet state, thousands of Russian citizens have been trafficked out of the country as exploited labour, sex slaves, domestic labour, and beggars. This project explored beliefs concerning the origins, nature and extent of human trafficking, and attitudes on what the Russian government should do to address the problem. It captured attitudes on how the state should aid the trafficked and the perceived efficacy of different institutions in dealing with trafficking. It also sought responses on how families should help or not help the trafficked; beliefs on the place of a woman in society, and attitudes towards prostitution. The data were collected through questions included in a nationwide public opinion poll, and through two focus groups conducted in Moscow (n=12) and Vladimir (n=8). The focus group transcripts are in Russian. English translations of the questionnaire and focus group schedule are included in the user guide.